Public health law : ethics, governance, and regulation / John Coggon, Keith Syrett, and A.M. Viens. - Coggon, John, 1980-; Syrett, Keith; Viens, A. M. (Adrian M.) (Routledge, 2017)
Public health activity, and the state's public health responsibilities to assure the conditions in which people can be healthy, can only be achieved through different means of social coordination. This places law and regulation at the heart of public health. They are fundamental both to methods of achieving public health goals, and to constraints that may be put on public health activity. As such, trainees, practitioners, and leaders in public health need to understand the breadth and nature of wide-ranging legal and regulatory approaches, and the place of ethics in public health. This title, written by three leading scholars in the field, defines and examines this crucial area of study and practice. It advances an agenda whose scope extends far beyond that covered in traditional medical law and health care law texts.